Implementasi Gaya Kepemimpinan Demokratis Kepala Sekolah Dalam Meningkatkan Kinerja Guru di SMK Muhammadiyah Majalaya - Alzahra, Tarisa Aidil; Irawan, Yusuf Cahya; Yoesyifa, Kheisya Aditya; Ramadhani, Rizky Amalia; Putri, Siti Rohaliani (Indonesian Journal Publisher, 2025)
The purpose of this study is to identify the implementation of a democratic leadership style by the principal of SMK Muhammadiyah Majalaya in enhancing teacher performance. Principal leadership plays a vital role in shaping a supportive environment for professional development, characterized by the ability to inspire, provide individual attention, and empower teachers to reach their potential. This research employed a qualitative approach using data collection techniques including participatory observation, in-depth interviews, and literature review. The findings reveal that the democratic leadership style adopted by the principal has significantly contributed to improved teacher performance, evident through their active involvement in school decision-making processes. Key characteristics of this leadership style include respect for individuals, granting rights and opportunities, promoting active participation, accommodating diversity, fostering collaboration, providing feedback and evaluation, openness to ideas and change, and supporting continuous professional growth. These practices have fostered a harmonious work environment, increased teacher motivation, and enhanced professional competence. In conclusion, the democratic leadership style not only strengthens internal school dynamics but also supports the realization of the institutional vision of SMK Muhammadiyah Majalaya by improving the quality of education and contributing positively to student learning outcomes.